Manajemen Laba: Konsep, Bukti Empiris dan Implikasinya - Primanita Primanita; Setiono Setiono (Universitas Islam Indonesia, 2006)
This paper is to review earning management from the academic evidence and its implication for accounting standard setters and regulators. Definition of earning management is that it occurs when management use judgement in financial reporting and in structuring transactions to alter financial reports to either mislead some stakeholders about underlying economic performance of the company or to influence contractual outcomes that depends on reported accounting numbers. Previous research was done to identify manager’s reporting incentives and factors that inflluence earning management, management motivation in doing earning management and investor reaction to these practices and specific accurals that was used to manage earning. The implication for standard setters and regulators is that academic findings should give insights on how far management is allowed to manage earnings. Key words: earning management, income smoothing, accruals